Human papillomavirus status and prognosis of oropharyngeal high-grade neuroendocrine carcinoma. (March 2023) - de Sousa, Luana G.; Lazar Neto, Felippe; Dal Lago, Eduardo A.; Sikora, Andrew; Hanna, Ehab; Moreno, Amy; Phan, Jack; Glisson, Bonnie S.; Bell, Diana; Ferrarotto, Renata
Highlights: HPV status does not affect OS in oropharyngeal high-grade neuroendocrine carcinoma. p16 is not a reliable surrogate marker for HPV infection in this population. HPV status should not guide therapy or de-escalation trials for this histology. Smoking does not affect OS in oropharyngeal high-grade neuroendocrine carcinoma. Abstract: Background: The prognostic impact of human papillomavirus (HPV) infection or smoking on oropharyngeal high-grade neuroendocrine carcinoma (HG-NEC) is not established. Methods: Retrospective study with patients with oropharyngeal HG-NEC seen at MD Anderson Cancer Center from 1997 to 2020, and previously reported patients with oropharyngeal HG-NEC and known p16 and HPV status from the literature review. Survival was estimated with the Kaplan-Meier method, and survival differences assessed with the log-rank test and Cox proportional hazards models. Results: Thirty patients were included; most had a heavy (≥10 pack-years) smoking history (52%), locoregional disease (stage III-IVB; 77%), and p16-positive tumor (92%). HPV was positive in 65% of tested samples (15/23). Of 24 patients treated with curative intent, the objective response rates was 90% (9/10) and 81% (17/21), respectively, for induction chemotherapy and definitive radiotherapy. During follow-up, 54% (13/24) recurred, mostly (11/13) at distant sites. Median overall survival (OS) was 46 months (95% CI, 14.3 - NA). OS was not associated with HPV status (HR 0.73, P = 0.6) or smoking (HR 1.16, P = 0.8). Among 63 patients with known HPV status after the literature review (19 HPV- and 44 HPV + ), HPV status remained unassociated with OS (P = 0.92). Conclusions: This is the largest retrospective cohort of oropharyngeal HG-NEC. Distant recurrence rate after curative treatment was high, suggesting that multimodality treatment including systemic therapy may benefit patients with locally advanced disease. HPV infection did not affect survival outcomes, therefore should not lead to therapy de-intensification for this histology.